Reducing deforestation and enhancing sustainability in commodity supply chains: interactions between governance interventions and cattle certification in Brazil - Alves Pinto, H.N.; Newton, Peter; Guedes Pinto, L.F. (Mongabay, 2015)
A large number of governance interventions are being developed in order to reduce deforestation and enhance the sustainability of commodity supply chains across the tropics. The extent to which individual agricultural commodity supply chain interventions can achieve scale, and environmental or social objectives, depends in part on the ways in which those interventions interact with other interventions. We use a case- study of the new Sustainable Agriculture Network (SAN) cattle certification program in Brazil to explore the different ways in which governance interventions interact. We examine the broad landscape of policies and programs that affect sustainability in the cattle supply chain in Brazil, and assess whether such interventions support or constrain the scaling up of the SAN cattle program. We conducted semi-structured interviews with key stakeholders from government, private sector, and civil society organizations. We found that multiple interventions are acting in a complementary manner to enhance sustainability and therefore enable the scaling up of the SAN program, by aiding compliance with environmental laws, adoption of good production practices, and improved monitoring. At the same time, limited development, implementation, and complementarity of some interventions could be antagonistic to the SAN program's expansion because they maintain a context in which many actors operate far below the sustainability criteria required by the program. Our holistic approach enables us to identify specific gaps in the complex landscape of governance interventions in Brazil. Greater strategic complementarity and coordination between interventions may catalyze a more coherent and effective pathway to reduced deforestation and enhanced sustainability.